2011
DOI: 10.3109/0142159x.2011.600360
|View full text |Cite
|
Sign up to set email alerts
|

Pre-training evaluation and feedback improve medical students’ skills in basic life support

Abstract: Background: Evaluation and feedback are two factors that could influence simulation-based medical education and the time when they were delivered contributes their different effects. Aim: To investigate the impact of pre-training evaluation and feedback on medical students' performance in basic life support (BLS). Methods: Forty 3rd-year undergraduate medical students were randomly divided into two groups, C group (the control) and pretraining evaluation and feedback group (E&F group), each of 20. After BLS th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
0
30
0
2
Order By: Relevance
“…This was similar to a report indicating that students who were evaluated prior to their training performed better in the post-training evaluation than a control group who had not been evaluated before training. [14] A limitation of this study was that, although the students seemed alarmingly overconfident, the data were unsuitable to statistically determine the correlation between competence (scores in percentages) and confidence (4 categories). An additional limitation was that individual feedback, as implied during supervised hands-on sessions, was not monitored.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to a report indicating that students who were evaluated prior to their training performed better in the post-training evaluation than a control group who had not been evaluated before training. [14] A limitation of this study was that, although the students seemed alarmingly overconfident, the data were unsuitable to statistically determine the correlation between competence (scores in percentages) and confidence (4 categories). An additional limitation was that individual feedback, as implied during supervised hands-on sessions, was not monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Because the outcome of skill performance in all 7 studies [53][54][55][56][57][58][59] demonstrated equivocal or minimal benefit in skill performance compared with traditional course format, we suggest the possibility of using other training methods for teaching BLS or ALS. However, the heterogeneity of the studies makes it unclear what this alternative method might be (weak recommendation, low-quality evidence).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For the important outcome of cognitive knowledge, we identified 4 RCTs: 2 were of very low quality (downgraded for serious risk of bias, imprecision, and possible publication bias), 53,54 1 was of low quality (downgraded for risk of bias and imprecision), 57 and 1 was of moderate quality (downgraded for imprecision). 55 These studies differed in the teaching methods used to compare cognitive outcome, including simulation (traditional course format), multimedia (computer-based learning), self-directed reading, limited instruction (larger student-to-instructor ratio), and self-directed computer-based learning.…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing traditional course format with training using computer-based instruction, self-directed learning, video-based instruction, and varied instructor-to-student ratios showed mixed results with regard to knowledge and skill at course completion and at reassessment up to 6 months after course completion. [132][133][134][135][136][137][138] These studies varied in course composition (paramedic students, medical students at various levels, nursing students, and credentialed healthcare providers), type of course (BLS or ALS), and instructional methods.…”
Section: Cpr Training In Resource-limited Environments Eit 634 -Newmentioning
confidence: 99%